Komisi Ombudsman Nasional: Problem dan Prospek - Susi Dwi Harjanti (Fakultas Hukum Universitas Islam Indonesia, 2002)
Having regardto the failure ofthe existing complaint system, the Wahid's administration govemment has formed anew institution in an effort to cover the weaknesses of the existing supervisory institutions. The new institution is the National Ombudsman Commission, which was established through the Presidential Decree Number 44 of 2000. Within twoyears ofits operation, the Ombudsman has receivedmore than 1, 723 complaints including those regarding the executive govemment officeras well as the judiciary. This may indicate that people puthigh expectationon this new Commission. How ever,apart from the impressive number of received complaints, there are some significant problem sfaced by this Commission tha tembrace, legal, politics as well associalim pediments. This article examines those problems and proposes some reforms